2015
DOI: 10.1007/s11095-015-1774-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Functional Evaluation of Increased Brain Delivery of the Opioid Peptide DAMGO by Glutathione-PEGylated Liposomes

Abstract: We were able to show that encapsulation into PEGylated liposomes of a peptide with limited brain delivery could double the drug uptake into the brain without using a specific brain targeting ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 29 publications
2
46
1
3
Order By: Relevance
“…A reduction in brain uptake was also observed in the study of quetiapine after nanoencapsulation. 8 Combined with our previous findings that certain types of PEG liposomes can improve the brain delivery of drugs with active efflux at the BBB, 5,6 it seems that liposomal encapsulation can influence BBB transport of drugs in different directions depending on how the drug interacts with the BBB. To be noted is that in our earlier study of MTX, only one of two liposomal formulations were able to increase brain uptake, indicating that in vivo delivery of drugs in liposomes is not a unified process.…”
Section: ■ Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A reduction in brain uptake was also observed in the study of quetiapine after nanoencapsulation. 8 Combined with our previous findings that certain types of PEG liposomes can improve the brain delivery of drugs with active efflux at the BBB, 5,6 it seems that liposomal encapsulation can influence BBB transport of drugs in different directions depending on how the drug interacts with the BBB. To be noted is that in our earlier study of MTX, only one of two liposomal formulations were able to increase brain uptake, indicating that in vivo delivery of drugs in liposomes is not a unified process.…”
Section: ■ Discussionmentioning
confidence: 71%
“…This enables simultaneous monitoring of the concentration− time profiles of released, unbound DPH in both brain and plasma, as well as total DPH in plasma. This study, combined with the previous work on MTX and DAMGO, 5,6 can provide quantitative elucidation on how the liposomes potentially affect the brain delivery of drugs with active influx or active efflux, which helps the in-depth understanding of how liposomes interact with the BBB.…”
Section: ■ Introductionmentioning
confidence: 84%
“…The need for superior targeted-drug carriers has been recently upgraded, since the tremendous therapeutic potential of biopharmaceuticals will become available only after formulation/delivery issues are resolved. Several types of nanoparticles (NPs), such as liposomes (Markoutsa et al, 2011(Markoutsa et al, , 2012De Luca et al, 2015;Lindqvist et al, 2016;Orthmann et al, 2016), solid-lipid NPs (Tosi et al, 2016), and polymeric NPs (Fornaguera et al, 2015) are under intense exploration, as systems to assist the delivery of drugs across the BBB, and the use of cellular models of the BBB is essential for acceleration of such studies. Recently, the human brain endothelial cells hCMEC/D3, have been shown to construct a BBB-alike monolayer under specific culturing conditions (Weksler et al, 2005;Poller et al, 2008), and its applicability as an in vitro system to screen brain targeted nanosized liposomes, has been verified (Markoutsa et al, 2011), although the monolayer they form could not be classified as "tight", since TEER values are <100 V cm À2 .…”
Section: Discussionmentioning
confidence: 99%
“…Again, DAMGO(H-Tyr-D-Ala-Gly-MePhe-Gly-ol), an opioid peptide with poor brain penetrating properties have been successfully encapsulated in glutathione (GSH)-coated liposomes. The biological activity was found to enhance in comparison to the empty GSH-PEG liposomes and the corresponding results suggested that the PEG liposomal DAMGO has been efficient in targeting brain without the use of any specific ligand [32]. Hydrophobic polyampholyte-modified liposomes, synthesized using a combination ofε -poly-L-lysine-dodecylsuccinic anhydride-succinic anhydride were compared with unmodified liposomes for the delivery of lysozyme.…”
Section: Liposomesmentioning
confidence: 99%